Introduction to information systems - Rainer, R. Kelly 4 0 (Rex Kelly)16; Turban, Efraim; 5 (Hoboken, NJ : John Wiley, 2009)
An introduction to information systems that shows how to apply information technology concepts to business processes in accounting, finance, marketing, management, human resources, and operations.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Information technology.;Information technology; 20; 2